Advisory services and preventive warning for internal audits - Calderón Ramos, Flora (2021)
The purpose of this research is to show how advisory and preventive services are approached by the Internal Audit Units (IAU), which is carried out under a quantitative and descriptive methodological approach, and is based on the results selected from a questionnaire of 50 questions, divided into the following categories of analysis that support the research: UAI methodologies used to provide warning services and preventive advice; utilities of this type of services; and difficulties that arise to be able to carry them out; applied to heads and collaborating technicians of 22 UAI of the Costa Rican public sector. The results obtained show that, for the most part, a management instrument is used to carry out these services. In addition, requests for advice or warnings that arise and are issued in accordance with the Costa Rican legal and technical system are permanently attended to.